Association between outdoor and indoor air pollutant exposure and depression among middle-aged and older adults in China - Zhixin Zhao; Yanting Chu; Xingtong Chen; Tao Liu (Scientific Reports)
Abstract Limited epidemiological studies have explored the association between outdoor and indoor air pollutants and depressive symptoms among middle-aged and elderly adults. We utilized data from the China Health and Retirement Longitudinal Study (CHARLS). Depressive symptoms were assessed using the 10-item Center for Epidemiologic Studies Depression Scale (CES-D 10), while indoor air pollution was self-reported. Outdoor air pollutant data were obtained from the China National Environmental Monitoring Center (CNEMC). Logistic regression was used to examine the association between exposure to outdoor air pollutants and indoor air pollutants from solid fuel use and depressive symptoms among middle-aged and older adults in China. The study found that each standard deviation (SD) increase in outdoor PM2.5 and SO2 was significantly associated with the occurrence of depressive symptoms. Exposure to indoor air pollution from solid fuel use for heating and cooking was also significantly linked to depressive symptoms. Indoor air pollution from solid fuel use for cooking may attenuate the association between outdoor PM2.5 and PM10 and depressive symptoms on a multiplicative scale. These findings highlight a significant correlation between depressive symptoms and exposure to both outdoor and indoor air pollutants in middle-aged and elderly adults.